PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA DI KELAS IV SD NEGERI 064025 KECAMATAN MEDAN TUNTUNGAN TAHUN PEMBELAJARAN 2018/2019 - PASARIBU, KRISTINA (Jurnal Ilmiah Aquinas, 2019)
The research is aimed to know the influence of parent’s education level on motivating the student’s match score year 2018/2019. The research is using the quantitative research by corelationmethode. The population in this study were all students of SD 064025 in Medan TuntunganSubdistrict as many as 734 people. The sample is 124 people with a sampling technique that is Simple Random Sampling.Data in research obtained is observations, questionnaire, and study documentation. The analytical technique used is a test of the prerequisite for analysis and hypothesis testing using the Program Statistics for Social Science (SPSS) assistance. From the data analysis data, it is found that there is a linear relationship between parent’s education level on motivating the student’s this is supported by the results of testingtcount>ttable and t test is done at the level (= 0,05) that tcount>ttablewas SD with SMP (2,2937 > 1,6675), SD with SMA (5,3917 > 1,6722), SD with D3 (2,2635 > 1,6779), SD with S1(2,0929 > 1,6810)this proves thatis accepted. Then there isinfluencebetweenparent’s education level on motivating learn the student’s in the fourth grade SD Negeri 064025 distric Medan Tuntungan.